STUDENTS IN CHARITY WORK - Borneo Post, (KK) (Borneo Post (KK), 2014)
STUDENTS IN CHARITY WORK: Distant learning students from Universiti Utara Malaysia Kota Kinabalu branch Neld a charity program at the Nur Muhammad Education and Welf are Organization, on June 21.Organizing chairman Ely Kevin Maten said the purpose of the event was to show that as Malaysians, they have the reponsibility to help those in need, adding thatthis was part of their assignment given by the university. Among the activities during the event were cleaning works and donations in the form of food. Picture shows the students with the orphans from the organization.